(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
A four-level inverted Y-type atomic system is subjected to three coherent laser fields simultaneously. The system has two closely spaced ground energy levels, one intermediate energy level and an uppermost energy level. Transition from the two ground levels to the intermediate level as well as from the intermediate level to the uppermost level are dipole allowed. Transition from the two ground energy levels to the uppermost level is dipole forbidden. A weak laser beam, known as the probe beam, acts between one of the ground levels and the intermediate level. A strong laser field, known as the control or pump field, couples the intermediate level with the uppermost level. A repump filed of intensity usually higher than the probe field acts between the other ground level and the intermediate level. The probe transmission through such a medium is investigated at different values of the control and repump Rabi frequencies under Doppler free condition as well as with thermal averaging. The nonradiative population transfer rates between the ground energy levels have been incorporated.